2014
DOI: 10.1002/ece3.1077
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific plant–soil feedback and intraspecific overyielding in Arabidopsis thaliana

Abstract: Understanding the mechanisms of community coexistence and ecosystem functioning may help to counteract the current biodiversity loss and its potentially harmful consequences. In recent years, plant–soil feedback that can, for example, be caused by below-ground microorganisms has been suggested to play a role in maintaining plant coexistence and to be a potential driver of the positive relationship between plant diversity and ecosystem functioning. Most of the studies addressing these topics have focused on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 68 publications
(166 reference statements)
1
37
0
1
Order By: Relevance
“…However, the individual accessions and species differed in the direction and strength of the feedback. With regard to intraspecific plant–soil feedback, we had formerly shown that A. thaliana accessions differ in the strength and direction of experienced feedback (Bukowski & Petermann, 2014). The same accessions in our experiment showed different feedback strengths and directions compared to this earlier study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the individual accessions and species differed in the direction and strength of the feedback. With regard to intraspecific plant–soil feedback, we had formerly shown that A. thaliana accessions differ in the strength and direction of experienced feedback (Bukowski & Petermann, 2014). The same accessions in our experiment showed different feedback strengths and directions compared to this earlier study.…”
Section: Discussionmentioning
confidence: 99%
“…However, most soil feedback studies refer to the interspecific level only, comparing growth of plants on own soil with growth on soil from other species. Recently, it has been shown that plant–soil feedback may operate at the intraspecific level, that is, that there are differences in plant growth on own soil compared with growth on soil from different accessions or genotypes within the same species (Bukowski & Petermann, 2014; Liu, Etienne, Liang, Wang, & Yu, 2015). Despite indications that certain pathogens may have similar effects on closely related species (Gilbert, Briggs, & Magarey, 2015; Parker et al., 2015), it is still unclear whether there is a difference in feedback strength between the intraspecific and the interspecific levels (van der Putten et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…; Hughes et al . ; Bukowski & Petermann ), there may be significant variation in the magnitude of such effects. Our study was unique in that we both sampled from tremendous phenotypic variation in a tree single species (by sampling genetic stock from throughout the range of the species), and out planted all genotypes in a single environment.…”
Section: Discussionmentioning
confidence: 99%
“…, Bowen et al. ), yet experiments examining intraspecific variation in PSFs remain rare (but see Bukowski and Petermann , Maron et al. , Wagg et al.…”
Section: Introductionmentioning
confidence: 99%